A little bait goes a long way: The influence of bait quantity on a temperate fish assemblage sampled using stereo-BRUVs - Hardinge, J.; Harvey, Euan; Saunders, Ben; Newman, Stephen (Elsevier, 2013)
Baited remote underwater video systems are becoming a widely adopted tool for sampling fish assemblages. One of the outstanding knowledge gaps associated with this technique is the effect of different quantities of bait on the fish assemblages sampled. We investigated how different quantities of bait (0 g, 200 g, 1000 g or 2000 g of crushed pilchards, Sardinops sagax) influenced the relative abundance and species richness of a temperate, Western Australian reef fish assemblage sampled with baited remote underwater stereo-video systems (stereo-BRUVs). The presence of bait significantly increased the relative abundance and numbers of fish species sampled, with few differences between the three quantities of bait. Trends in fork length were identified between bait quantities for some species. For example, juvenile stage Coris auricularis (a protogynous labrid) were significantly larger in the unbaited treatment,whereas males of the same specieswere significantly smaller at unbaited treatments. This pattern was interpreted as being the result of intraspecific competition and the dominance of larger males in the presence of bait. When bait was present, fish were significantly closer to the stereo-BRUVs. However, there was again no difference between the three baited treatments.At this location in temperateWestern Australia, stereo-BRUVs with 200 g of bait are as effective at sampling the temperate reef fish assemblage as stereo-BRUVs set with greater quantities of bait. In our study, the numbers of high trophic level species recorded were low. In areas with abundant high trophic level fishes, such as tropical reef systems, greater quantities of bait may be required to prevent it being quickly depleted by intense feeding.